Video head impulse test in children after cochlear implantation - Lemajic-Komazec, Slobodanka N; Komazec, Zoran S.; Vlaški, Ljiljana M.; Buljčik-Čupić, Maja M.; Savović, Slobodan N.; Mihajlović, Dunja M.; Sokolovac, Ivana V. (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Cochlear implantation (CI) is a therapeutic modality that provides a sense of sound to children and adults with profound sensorineural hearing loss or deafness. The aim of this work was to evaluate the lateral semicircular canal function using a high frequency video head impulse test in children after CI. Methods. A prospective descriptive study included 28 children (6–17 years old) with profound sensorineural hearing loss and unilateral CI. The control group included 20 healthy children with normal hearing. The measurement of vestibular function of the lateral semicircular canal was performed using video head impulse test. After cochlear implantation, the children underwent the vestibular testing. Values vestibulo-ocular reflex of lateral semicircular canal were measured using the video head impulse test in the children with cochlear implant and the control group. The values of vestibulo-ocular reflex were compared between the group. Also, in the children with CI values of vestibulo-ocular reflex were compared between the non-implanted ear and the ear with the embedded CI. Results. All 28 children with sensorineural hearing loss underwent the placement of CI through cochleostomy at the average age of 4.8 ± 2.92 years. Children with the cochlear implant had a significantly lower vestibulo-ocular reflex gain of the lateral semicircular canal measured by a high frequency video head impulse test compared to the control group of children with normal hearing (T test: t = 3.714; p = 0.001). However in these children there was no statistically significant difference of vestibulo-ocular reflex gain in the lateral semicircular canal measured in ears with embedded CI and non-implanted ears (T test: t = 0.419; p = 0.677). Conclusion. The values of vestibulo-ocular reflex gain in the lateral semicircular canal evaluated by the video head impulse test are significantly lower in the children with a profound sensorineural hearing loss compared to the children with normal hearing. The CI did not appear to have a negative impact on the lateral semicircular canal.